Novel Molecular-Dynamics-Based Protocols for Phase Space Sampling in Complex Systems - Mai, Sebastian; Gattuso, Hugo; Monari, Antonio; González, Leticia (Frontiers in Chemistry, 2018)
The adequate exploration of the phase space of a chromophore is a fundamental necessity for the simulation of their optical and photophysical properties, taking into account the effects of vibrational motion and, most importantly, the coupling with a (non-homogeneous) molecular environment. A representative set of conformational snapshots around the Franck-Condon region is also required to perform nonadiabatic molecular dynamics, for instance in the framework of surface hopping. Indeed, in the latter case one needs to prepare a set of initial conditions providing a meaningful and complete statistical base for the subsequent trajectory propagation. In this contribution, we propose two new protocols for molecular dynamics-based phase space sampling, called “local temperature adjustment” and “individual QM/MM-based relaxation”. These protocols are intended for situations in which the popular Wigner distribution sampling procedure is not applicable—as it is the case when anharmonic or nonlinear vibrations are present—and where regular molecular dynamics sampling might suffer from an inaccurate distribution of internal energy or from inaccurate force fields. The new protocols are applied to the case of phase space sampling of [Re(CO)3(Im)(Phen)]+ (im = imidazole, phen = phenanthroline) in aqueous solution, showing the advantages and limitations of regular Wigner and molecular dynamics sampling as well as the strengths of the new protocols.